2020
DOI: 10.1016/j.devcel.2020.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Microscopy and FIB-SEM Imaging Reveal Parental Centriole-Derived, Hybrid Cilium in Mammalian Multiciliated Cells

Abstract: Motile cilia are cellular beating machines that play a critical role in mucociliary clearance, cerebrospinal fluid movement, and fertility. In the airways, hundreds of motile cilia present on the surface of a multiciliated epithelia cell beat coordinately to protect the epithelium from bacteria, viruses, and harmful particulates. During multiciliated cell differentiation, motile cilia are templated from basal bodies, each extending a basal foot-an appendage linking motile cilia together to ensure coordinated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…9 Our findings highlight the role of PC in the process of AEC differentiation. This is particularly important as a recent study demonstrated the presence of a hybrid cilium in MCC with PC features, 10 and PC functions are discussed in several respiratory diseases including COPD, asthma and idiopathic pulmonary fibrosis. 2,11,12 Given that PC are involved in many signalling pathways, a better understanding of their involvement in lung physiology and pathologies may help identify crucial molecular actors to expand diagnosis, prognosis and therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Our findings highlight the role of PC in the process of AEC differentiation. This is particularly important as a recent study demonstrated the presence of a hybrid cilium in MCC with PC features, 10 and PC functions are discussed in several respiratory diseases including COPD, asthma and idiopathic pulmonary fibrosis. 2,11,12 Given that PC are involved in many signalling pathways, a better understanding of their involvement in lung physiology and pathologies may help identify crucial molecular actors to expand diagnosis, prognosis and therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the role of PC in the process of AEC differentiation. This is particularly important as a recent study demonstrated the presence of a hybrid cilium in MCC with PC features, 10 and PC functions are discussed in several respiratory diseases including COPD, asthma and idiopathic pulmonary fibrosis 2,11,12 …”
Section: Discussionmentioning
confidence: 99%
“…The cilium is a complex organelle exerting its function with molecular machinery that may only be resolved with electron microscopy. Recently, super-resolution microscopy coupled with focused ion beam scanning electron microscopy (FIB-SEM) demonstrated the presence of a hybrid cilium in MCC [ 33 ]. Exploring the structural abnormalities of all types of cilia in the context of respiratory diseases may contribute to the identification of new biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that a balance of force model, in which different forces – exerted by the actin and microtubule cytoskeletons – are balanced by the concerted anchoring of several centriole appendages ( Basquin et al, 2019 ). Interestingly, both rootlets and basal feet appear capable of changing their structure in response to force in certain biological contexts ( Liu et al, 2020 ; Soh et al, 2020 ). Ciliate rootlets change length and orientation depending on cilia-generated force, apparently to maintain centrosomal connections and cortical interactions over a timescale of hours ( Galati et al, 2014 ; Soh et al, 2020 ).…”
Section: Positioning and Linking Multiciliary Arraysmentioning
confidence: 99%